PENGARUH GREEN PRODUCT, GREEN PRICE, DAN ENVIRONMENTAL AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP DI KOTA SURAKARTA - Adhila Inyustisia; Saryadi Saryadi; Sari Listyorini (Universitas Diponegoro, 2024)
In recent years, concern about the importance of the environment has been increasingly influencing the business world. The awareness of environmentally friendly products is increasing as well as global cosmetic companies that care about nature and have social and environmental values, as well as natural ingredients such as The Body Shop's products. The Body Shop's Body Mist and Body Butter products have been the Top Brands since 2019 in the personal care category and in 2021 received a score of 49.6% and 44.4% respectively. However, in 2022 the index will decrease to 44.9% and 41.5%. The purpose of this study was to determine the effect of green product, green price, and environmental awareness on consumer purchasing decisions. This type of research is explanatory research with a sample size of 96 respondents, taken using non-probability sampling techniques and accidental sampling research methods. The results showed that green product, green price, and environmental awareness have an effect on consumer purchasing decisions. This research supports the theory of consumer behavior in the purchasing decision process. The limitation of this research is that still too general in its implementation because it is not specific yet to a particular product of the research object. Suggestions for further research can be carried out in other regions to get diverse results and can add other variables such as brand image.Keywords: green product; green price; environmental awareness; purchase decisionBeberapa tahun ini, perhatian terhadap pentingnya lingkungan semakin memberi pengaruh dalam dunia bisnis. Kesadaran akan produk environmentally friendly semakin meningkat seperti halnya perusahaan kosmetik global yang peduli pada alam dan memiliki value terhadap sosial dan lingkungan, serta kandungan bahan alami seperti produk yang dimiliki The Body Shop. Produk Body mist dan Body Butter The Body Shop masuk menjadi Top Brand sejak tahun 2019 pada kategori perawatan pribadi dan tahun 2021 mendapat masing-masing skor 49,6% dan 44,4%. Namun pada tahun 2022 mengalami penurunan index menjadi 44,9% dan 41,5%. Tujuan penelitian ini untuk mengetahui pengaruh green product, green price, dan environmental awareness terhadap keputusan pembelian konsumen. Jenis penelitian ini adalah explanatory research dengan jumlah sampel sebanyak 96 responden, diambil menggunakan teknik non-probability sampling dan metode penelitian accidental sampling. Analisis data dilakukan menggunakan Software SPSS Statistics 26. Hasil penelitian menunjukkan green product, green price, dan environmental awareness berpengaruh terhadap keputusan pembelian konsumen. Penelitian ini mendukung teori perilaku konsumen dalam proses keputusan pembelian. Keterbatasan penelitian ini adalah masih terlalu general pada pelaksanaanya karena belum spesifik pada produk tertentu dari objek penelitian. Saran untuk penelitian selanjutnya dapat dilakukan dengan menambahkan variabel lain seperti kualitas produk.Kata Kunci: green product; green price; environmental awareness; keputusan pembelian